Anticorpos em eritrócitos e plaquetas em cães naturalmente infectados por Rangelia vitalii - França, Raqueli Teresinha (2015)
Rangeliosis was first described in 1908, despite the elapsed time after its discovery, it is a reemergent disease. So far they have been reported in Brazil, mainly in the southern region of the country, Argentina and Uruguay. Currently it is known that this disease only occurs in domestic and wild canids. Rangeliosis is caused by the protozoan Rangelia vitalii, transmitted to dogs by ticks Amblyomma aureolatum. The main laboratory findings of infection Rangelia vitalii are anemia and thrombocytopenia. The mechanisms involved in anemia and thrombocytopenia are still not well understood. Thus, the objective of this study was to describe a review of the rangeliosis since its discovery to the present day and investigate the involvement of the immune system in the pathogenesis of anemia and thrombocytopenia in dogs with Rangelia vitalii through the detection of IgM and IgG on the surface of erythrocytes and platelets, and also assess the regenerative response by determining percentage of reticulocytes and reticulated platelets. For this, blood samples from twenty dogs attended hospital routine were used. The samples were collected from animals aged 11 months and 3 years, male and female, of different breed. The samples were divided into two groups and infected control. The infected group was composed of 10 blood samples from dogs diagnosed with rangeliosis. The control group consisted of blood samples from 10 clinically healthy dogs, treated at the HVU for elective surgery. Animals with rangeliosis showed moderate to severe thrombocytopenia and normocytic normochromic anemia. In dogs infected with Rangelia vitalii there was an increase in the percentage of reticulated platelets and increase in IgM antibody percentage on the surface of platelets in the control group. Already, for IgG antibody bound to the surface of platelets was no statistical difference between the groups. There was no significant difference in the percentage of reticulocytes and not in IgM and IgG antibody attached to the surface of red blood cells compared to the control group. From these results, it is concluded during infection by Rangelia vitalii IgM antibody binding occurs on the surface of platelets. Antibody binding can affect both platelet function as lead to an early and rapid destruction of these cells by the phagocytic system is increased reticulated platelets, indicating active thrombopoietic. IgG and IgM antibodies are not involved in the pathogenesis of hemolytic anemia in the initial stage of the disease. However, do not rule out the possibility of involvement of other mechanisms that contribute to anemia and thrombocytopenia observed in rangeliosis.